Analisis Kesehatan Mental Pada Lansia (Memahami Kebersyukuran Pada Lansia Muslim di Aceh Utara) - Zurratul Muna; Liza Adyani (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2020)
This study aims to see a picture of mental health based on the aspects of gratitude, namely: the meaning of gratitude, the factors that affect gratitude and the application of gratitude by the elderly. This research is a type of qualitative research with an exploratory approach to be able to understand the mental health picture in the elderly. The population in this study were elderly Muslims in North Aceh Regency. The sampling technique in this study using purposive sampling technique, namely the criteria: 1. Male or female aged 60 years or more and 2. Native residents of North Aceh Regency. Data collection techniques used in this study include semi-structured interviews and Focus Group Discussion (FGD). The method of data analysis in this study is to use several steps, namely: 1) processing the data, 2) reading the entire data; 3) analyze in more detail by coding the data; 4) implementing the coding process; and 5) show how these descriptions and themes will be restated in a qualitative narrative / report. The result of this research is that gratitude is a positive expression because individuals have a better meaning for their lives because they are able to accept all the provisions determined by Allah, both those that match their expectations and those that do not. The factors that influence the emergence of a sense of gratitude in the elderly are by getting closer to Allah by carrying out all his commands, both obligatory and sunnah.